Legume Cover Crop Planting in Slope Area with Templok Method in Gunung Walat Education, Sukabumi - Lika Aulia Indina; Yadi Setiadi (Jurnal Silvikultur Tropika, 2011)
Legume  Cover  Crop  establishment  is  vegetative  method for  erosion  control  in  the  slope  area.  Calopogonium mucunoides, Centrosema pubescens, and Pueraria javanica are the species  are uses as mixed  Legume Cover Crop for erosion control. The problem in cover crop planting on slope area is the seed easy wash away by the rain, so erosion control in the slope area can not be implemented properly. The Templok Method is a new method for planting Legume Cover Crop in the slope area. This method use TeraGlue as kohesif material, for straw or litter as planting media and cocofiber net. This research done at area with  ± 70° slope in Gunung Walat Forest Education, Sukabumi.           The result of this research indicate that Templok Method by using TeraGlue, straw and litter media also cocofiber net can give good effect of planting Legum Cover Crop in the slope area. Based on this first research, Templok Method can be use as alternative solution for planting Legum Cover Crop for erosion control in slope area.